Prevalence of ATM Sequence Variants in Northern Plains American Indian Cancer Patients - Petereit, Daniel G. (Frontiers in Oncology, 2013)
Purpose: To identify sequence variants of the ataxia telangiectasia mutated (ATM) gene and establish their prevalence rate among American Indian (AI) as compared with non-AI cancer patients. Materials and Methods: DNA was isolated from blood samples collected from 100 AI and 100 non-AI cancer patients undergoing radiation therapy, and a blinded assessment of the ATM sequence was conducted. Quantitative PCR assessment of copy number for each exon was also performed. The main outcome measure was the prevalence of ATM variants in the two patient populations. Results: No statistically significant differences for total prevalence of ATM variants among AI and non-AI patients were found. Of the 25 variants identified, five variants had a prevalence of >2%, of which 4 occurred at a rate of >5% in one or both groups. The prevalence of these four variants could meaningfully be compared between the two groups. The only statistically significant difference among the groups was the c.4138C>T variant which is predicted not to affect protein function, seen in 8% of AI versus 0% of non-AI patients (P=0.007). No exonic copy number changes were found in these patients. Conclusions: This study is the first to determine the prevalence of ATM variants in AIs.